2020
DOI: 10.1016/j.pcd.2020.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Falls in older people with diabetes: Identification of simple screening measures and explanatory risk factors

Abstract: Aims: To identify risk factors for falls in older people with diabetes mellitus (DM) and to develop a low-cost fall risk screening tool.Methods: Older adults with DM (n=103; age=61.6+6.0years) were recruited from diabetic clinics. Demographic, DM specific factors, lower limb strength and sensation, cognition, fear of falling, hand reaction time, balance, mobility and gait parameters were assessed using validated methods. Falls were prospectively recorded over six months.Results: Past falls and female gender we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Anoter research reported that female gender increases the risk by 4.62%. 25 Results of our study concluded that majority of the patients (55.95) were at medium risk of fall. Our research findings were similar to another study which reported 84% were at medium risk of fall and 15% were at mild risk of fall among total 196 diabetic patients.…”
Section: Discussionmentioning
confidence: 60%
“…Anoter research reported that female gender increases the risk by 4.62%. 25 Results of our study concluded that majority of the patients (55.95) were at medium risk of fall. Our research findings were similar to another study which reported 84% were at medium risk of fall and 15% were at mild risk of fall among total 196 diabetic patients.…”
Section: Discussionmentioning
confidence: 60%
“…Wettasinghe et al. reported that increased postural sway with eyes open and closed was significantly associated with falls ( 33 ). Most postural sway parameters in the older age group were significantly higher than those in the relatively younger group from this study.…”
Section: Discussionmentioning
confidence: 99%
“…202 In a recent assessment centred on balance and falls, three fourths of multiple-faller patients had a diagnosis of neuropathy. 203 These exhibited objectively increased body sway with or without vision, standing on solid ground or foam, and walking speed was slower than in patients who did not fall. In this regard, it has been found in a study that recruited patients of different age groups that the tactile pressure sensitivity threshold increases significantly across the entire foot sole with age, with the larger loss of sensitivity at the heel than at the forefoot.…”
Section: Balance and Falls In Diabetic Patientsmentioning
confidence: 94%